Age and Household Solid Waste Arising in Suburban Malaysia: A Statistical Approach - Irwan D.; Basri N.E.A.; Watanabe K.; Ahmed A.N. (Springer Science and Business Media Deutschland GmbH, 2023)
Solid wastes; Statistical methods; Age; Aging societies; Household solid waste; Malaysia; Multi-layered; Per capita; Socio-economics; Solid waste generation; Statistical approach; Sustainable cities; Surveys